The effect of Wolbachia on gene expression in Drosophila paulistorum and its implications for symbiont-induced host speciation - Baião, Guilherme C. (BMC Genomics, 2019)
BACKGROUND: The Neotropical fruit fly Drosophila paulistorum (Diptera: Drosophilidae) is a species complex in statu nascendi comprising six reproductively isolated semispecies, each harboring mutualistic Wolbachia strains. Although wild type flies of each semispecies are isolated from the others by both pre- and postmating incompatibilities, mating between semispecies and successful offspring development can be achieved once flies are treated with antibiotics to reduce Wolbachia titer. Here we use RNA-seq to study the impact of Wolbachia on D. paulistorum and investigate the hypothesis that the symbiont may play a role in host speciation. For that goal, we analyze samples of heads and abdomens of both sexes of the Amazonian, Centro American and Orinocan semispecies of D. paulistorum. RESULTS: We identify between 175 and 1192 differentially expressed genes associated with a variety of biological processes that respond either globally or according to tissue, sex or condition in the three semispecies. Some of the functions associated with differentially expressed genes are known to be affected by Wolbachia in other species, such as metabolism and immunity, whereas others represent putative novel phenotypes involving muscular functions, pheromone signaling, and visual perception. CONCLUSIONS: Our results show that Wolbachia affect a large number of biological functions in D. paulistorum, particularly when present in high titer. We suggest that the significant metabolic impact of the infection on the host may cause several of the other putative and observed phenotypes. We also speculate that the observed differential expression of genes associated with chemical communication and reproduction may be associated with the emergence of pre- and postmating barriers between semispecies, which supports a role for Wolbachia in the speciation of D. paulistorum. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12864-019-5816-9) contains supplementary material, which is available to authorized users.